2019
DOI: 10.1159/000495988
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Study of PCI-27483, a Factor VIIa Inhibitor in Combination with Gemcitabine for Advanced Pancreatic Cancer

Abstract: Objectives: Tissue factor overexpression is associated with tumor progression, venous thromboembolism, and worsened survival in patients with cancer. Tissue factor and activated factor VII (FVIIa) complex may contribute to tumor invasiveness by promoting cell migration and angiogenesis. The study objective was to evaluate safety, pharmacokinetics, and efficacy of PCI-27483, a selective FVIIa inhibitor. Methods: This was an open-label, multicenter phase 2 trial of patients with advanced pancreatic cancer. Part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…An FXa inhibitor, rivaroxaban, did not directly affect the growth of TF-positive pancreatic cancer xenografts in immunodeficient mice [ 194 ], but did suppress tumor growth in an immunocompetent setting that was partially dependent on reprograming tumor-associated macrophages [ 195 ]. A selective small molecule inhibitor of FVIIa, PCI-27483, inhibited tumor growth in preclinical models [ 196 ], although combining it with gemcitabine was not clearly superior to gemcitabine alone in a phase 2 clinical trial against pancreatic cancer [ 197 ].…”
Section: Tissue Factor As a Target For Cancer Therapymentioning
confidence: 99%
“…An FXa inhibitor, rivaroxaban, did not directly affect the growth of TF-positive pancreatic cancer xenografts in immunodeficient mice [ 194 ], but did suppress tumor growth in an immunocompetent setting that was partially dependent on reprograming tumor-associated macrophages [ 195 ]. A selective small molecule inhibitor of FVIIa, PCI-27483, inhibited tumor growth in preclinical models [ 196 ], although combining it with gemcitabine was not clearly superior to gemcitabine alone in a phase 2 clinical trial against pancreatic cancer [ 197 ].…”
Section: Tissue Factor As a Target For Cancer Therapymentioning
confidence: 99%
“…This trial has been completed and though the combination was well tolerated, there was no demonstrated efficacy. 42 PCI-27483 was first identified as a drug repurposing candidate as an inhibitor of TMPRSS2 by using a structure-based phylogenetic computational tool called 3DPhyloFold to identify structurally similar serine proteases, such as FVIIa, with known inhibitors that docked well to the TMPRSS2 structural model. 43 Later, PCI-27483 was identified and confirmed to be an inhibitor of TMPRSS2 by NCATS scientists using a structural modeling and binding-site analysis of TMPRSS2, followed by a structure-based virtual screening and molecular docking approach.…”
Section: Resultsmentioning
confidence: 99%
“…This study randomized 34 patients with metastatic or locally advanced PC to receive PCI-27483-GEM (n = 18) or GEM alone (n = 16). OS did not significantly differ between patients treated with PCI-27483-GEM and those with GEM alone but there was a nonsignificant trend toward longer PFS in patients receiving PCI-27483-GEM compared to those receiving GEM alone (PFS: 3.7 months vs. 1.9 months; HR 0.62; p = 0.307) [99]. There was no difference in the rates of grade ≥3 bleeding between the two arms and there was a trend toward lower rates of VTE in the PCI-27483-GEM arm (6% vs. 13% in the GEM arm).…”
Section: Anticoagulants As Adjuvant Treatment To Improve Survival In mentioning
confidence: 85%